Analisis Kepuasan Konsumen pada Foto Copy Kurnia Jaya Sangatta - Mery Oktavia Giawa; Meita Sondang Riski (Jurnal EKSIS, 2022)
The purpose of this study was to analyze consumer satisfaction on Photocopy of Kurnia Jaya Sangatta. The analysis uses descriptive statistics where the data is processed using SPSS version 21. The results of the study are proven from 96 respondents who answered the questions asked, the average answer was satisfied. In terms of data validity and reliability, the results of the study show that all indicators of satisfaction variables given a photocopy of Kurnia Jaya Sangatta proved valid and reliable. The conclusion of this study is that consumers feel satisfied while using the photocopy service of Kurnia Jaya Sangatta, both seen from the photocopying results and the services provided. This consumer satisfaction can be seen from the average respondents' answers above 49% answered satisfied. In terms of consumers wanting to use photocopying services and wanting to recommend, the average respondent's answers above 45% answered that they were willing. As for the problem of complaints or complaints, the average respondent's answers above 47% answered that they did not want to complain and if there were consumers who complained, consumers believed that the Kurnia Jaya shop owner was willing to accommodate their complaints.